2019
DOI: 10.1017/s1041610219001315
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of short Beck Hopelessness Scale in psychological autopsy study among Chinese rural elderly

Abstract: Background:Older adults represent the segment of population most exposed to the risk of suicide nearly everywhere in the world. Previous studies showed that hopelessness was an important risk factor for suicide.Aims:This study aimed to evaluate the reliability and validity of the four-item Beck Hopelessness Scale (BHS-4) in psychological autopsy study among Chinese rural elderly.Method:Two-stage stratified cluster sampling method was used to select research sites. Using case-control psychological autopsy study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
0
14
0
6
Order By: Relevance
“…Psychological autopsy has been shown to be an effective method for thoroughly assessing an individual's state of mind and life circumstances postmortem to investigate suicide deaths (Weinberger et al, 2018). Thus, family member informants are able to provide accurate information about the decedent's medical history (Klinkenberg et al, 2003), the presence of psychotic disorders and mood disorders (Sundqvist et al, 2008), and even internal states such as hopelessness (Ma et al, 2020). Furthermore, research has found a high level of agreement when psychological autopsy procedures are evaluated using a sample of living depressed psychiatric inpatients as compared with their family member informants (DeJong & Overholser, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Psychological autopsy has been shown to be an effective method for thoroughly assessing an individual's state of mind and life circumstances postmortem to investigate suicide deaths (Weinberger et al, 2018). Thus, family member informants are able to provide accurate information about the decedent's medical history (Klinkenberg et al, 2003), the presence of psychotic disorders and mood disorders (Sundqvist et al, 2008), and even internal states such as hopelessness (Ma et al, 2020). Furthermore, research has found a high level of agreement when psychological autopsy procedures are evaluated using a sample of living depressed psychiatric inpatients as compared with their family member informants (DeJong & Overholser, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For BHS-4, the subject–proxy agreement was good (ICC = 0.682). The Cronbach's alpha was 0.834 ( 27 ). Moreover, the subject–proxy agreements on pain intensity (ICC = 0.504) and perceived burden (ICC = 0.487) were fair.…”
Section: Methodsmentioning
confidence: 99%
“…34 Mental health professionals with expertise in post-mortem work conceptualize each case until a consensus is reached. 35 Psychological autopsies are reliable and valid for determining psychological diagnoses 26 and psychological states 36 of individuals who have died by suicide. As recommended for psychological autopsy research, 37 the present assessment included structured interviews with family members, medical examiner’s report, police report, suicide notes, prior medical and psychiatric records, and autopsy toxicology results.…”
Section: Methodsmentioning
confidence: 99%